If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -23ba + a = 17b Reorder the terms: a + -23ab = 17b Solving a + -23ab = 17b Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Combine like terms: 17b + -17b = 0 a + -23ab + -17b = 0 The solution to this equation could not be determined.
| 36x^2-33x-108=0 | | 27x^12y^10= | | 6n^2-168=18n | | 1.5y+10=1 | | -8k=24 | | x^2+12x-74=0 | | 12=10x-4-12x | | 10=t^2-8t | | 100s+20=460 | | A^2+23a-42=0 | | -8a(3-4b+7c)= | | 2(x-5)=4x-2(x+5)-1 | | 4*-z= | | H(t)=-16t^2+vt+h | | 5w+15=-3 | | 4*w= | | 11y-9y+15=11 | | 3x^4-10x^3-2x^2-6=0 | | 4a^2-5=10 | | 3n-12=9n | | 5x^2+10x=50 | | -3t*6= | | -2x^2-9x+10=0 | | 9x+12y=747 | | 88x-81=4x(5*2-10)-81 | | 4(x-3)=8-5x | | 2x+(3x^2-x-1)=1 | | C=20+5h | | 2(x+5)=1x-8 | | -1(x^2+6x+5)=0 | | 72=8a | | 10+2z=58-6z |